Radiofrequency Ablation versus Liver Resection for Colorectal Cancer Liver Metastasis: An Updated Systematic Review and Meta-analysis - Han, Yue (Chin Med J (Engl), 2016)
BACKGROUND: Controversial results about the therapeutic value of radiofrequency ablation (RFA) and liver resection (LR) in the treatment of colorectal cancer liver metastasis (CRCLM) have been reported. Thus, we performed the present meta-analysis to summarize the related clinical evidences. METHODS: A systematic literature search was conducted using PubMed (Medline), EMBASE, Cochrane Library, and Web of Science, for all years up to April 2016. Pooled analyses of the overall survival (OS), progression-free survival (PFS), and morbidity rates were performed. RESULTS: A total of 14 studies were finally enrolled in the meta-analysis. Patients treated by LR gained a longer OS and PFS than those of patients treated by RFA. Patients in the RFA group had lower morbidity rates than those of patients in the LR group. Publication bias analysis revealed that there was no significant publication bias in the meta-analysis. CONCLUSIONS: Patients with CRCLM gained much more survival benefits from LR than that from RFA. RFA rendered lower rates of morbidities. More well-designed randomized controlled trails comparing the therapeutic value of LR and RFA are warranted.